A case of Jarisch–Herxheimer reaction in candidiasis treated with systemic fluconazole. Issue 2 (17th February 2020) - Muscianese, Marta; Magri, Francesca; Pranteda, Giulia; Pranteda, Guglielmo
Abstract: Jarisch–Herxheimer reaction (JHR) is an acute and self‐limited condition, which commonly occurs after treatment for spirochetal infections. Probably, it corresponds to a transient immunological reaction to endotoxin‐like products released from the microorganism during the therapy. For this reason, JHR may be associated with many other infectious diseases besides syphilis. Here, we report a case of a patient affected by extended cutaneous candidiasis diagnosed by culture examination; a JHR occurred after an accidental overdose of oral fluconazole.